2012
DOI: 10.1021/jp210269m
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Surface-State Emission of CdSe Quantum Dots and Its Application to Microscale Luminescence Patterns

Abstract: In this paper, we report distinct enhancement of surface-state emissions (SSEs) of colloidal CdSe quantum dots (QDs) via coupling to localized plasmons (LPs) in Ag nanostructures. The roles of oleic acid (OA) ligand on QDs in the formation of Ag nanostructures and in the intense enhancement of SSEs of CdSe QDs are explored. We find that OA ligand on CdSe QDs plays a critical role in modifying the morphology of the contacted Ag, which consequently impacts the coupling of QD emitters with LPs in Ag. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…A key issue arises here, namely, can we convert the non‐radiative trap states to radiative ones? Recently, the surface trap states of CdSe QDs have been effectively converted to radiative ones by plasmon‐resonance methods and the QY of these QDs was greatly enhanced . Studies have shown that colloidal QDs with rich surface trap states could be used as white‐light sources because surface trap states can generate a high‐QY broad emission band in the visible region; furthermore, they can be changed by some external parameters …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key issue arises here, namely, can we convert the non‐radiative trap states to radiative ones? Recently, the surface trap states of CdSe QDs have been effectively converted to radiative ones by plasmon‐resonance methods and the QY of these QDs was greatly enhanced . Studies have shown that colloidal QDs with rich surface trap states could be used as white‐light sources because surface trap states can generate a high‐QY broad emission band in the visible region; furthermore, they can be changed by some external parameters …”
Section: Introductionmentioning
confidence: 99%
“…However, post‐synthesis wet‐chemical treatments usually introduce more defects on the surface of the QDs and form rich‐surface trap states, which usually additionally quench the luminescence. Whereas surface states are dominant routes in the non‐radiative decay of excited electrons, the resonant coupling of QD emitters‐metallic plasmons provides an effective way for extracting the energy of the surface states via radiative decay channels . This physical approach greatly enhances the intensity of SSE.…”
Section: Introductionmentioning
confidence: 99%
“…XRD characterization shows that the Ag films annealed in OA have better crystallinity favorable for the #3 QDs SSE enhancement. Adapted from Hu et al (2012a). enhanced SSEs observed in the QDs/Ag/Si hybrid structures are similar to those of the acceptors in resonance energy transfer systems (Sadhu et al, 2010). SSs on CdSe CQDs are usually thought to be an essential path for nonradiative relaxation (Hines and Guyot-Sionnest, 1996).…”
Section: Mechanism Of Plasmons In Ag Nanostructures Coupled With Cqdsmentioning
confidence: 92%
“…Adapted fromHu et al (2012a). Each row corresponds to one of the three groups of QDs (#1, #2, and #3 from top to bottom).…”
mentioning
confidence: 99%
See 1 more Smart Citation